On Psychotherapy of Non-collaborative Children - K. Nováková; P. Němečková; Z. Kolařík; S. Richterová (Czech Dental Chamber, 2005)
In a longitudinal study the authors follow the possibilities of positively influencing the behavior in 258 non-collaborative children in a dental office. The efficiency in the scale of psychotherapeutic procedures and methods is evaluated, in cases of failure premedication is administered and if necessary the treatment is performed in general anesthesia in relation to age and intellectual level. Psychotherapy was successfully applied during the entry examination of the admitted patients in almost a half of the cohort (43.4%), one third of the cohort was treated in general anesthesia. No problem behavior was encountered in 55.5% of the whole cohort during the final treatment.The behavior without problems was most frequent in individuals intellectually within normal range (in 81.2%), less frequently in children of special schools (32.1%), whereas in individual not attending school there was no adjustment of behavior.